The Impact of the Variation of Digital Story's Presentation Patterns (static graphics\ animations) in Problem-Solving Based Learning on Developing Computer Skills for Middle-School Female Students - Alzughaibi, Imtinan Mohammed; Alshuwaie, Mohammed Ibrahim (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the effect of different Pattern of presenting digital stories (static graphics, animations) on problem-based learning to develop computer skills among middle school students. The study followed the experimental approach, and the sample consisted of (60) female students who were randomly selected from the first intermediate grade students from the first and second middle school in Al-Bukayriyah in the Kingdom of Saudi Arabia, and was divided into two experimental groups such that (30) students for each group. The study tools were the achievement test to measure the cognitive aspect associated with computer skills and the observation card to measure the performance aspect of computer skills, with the preparation of digital stories in order to develop the skills of operating and connecting a computer device with two Patterns (static graphics, animations), and the data was processed using the statistical package program (SPSS) and the results showed that there are statistically significant differences between the average scores of the students of the two experimental groups in favor of the experimental group with a pattern (static graphics) in the achievement test and the observation card. The study recommended benefiting from the results in the renewal in the methods of providing skills in computer courses and adopting the idea of computerizing curricula in addition to activating the problem-solving method in teaching computer skills to middle school students, also conducting research and studies similar to the current study using other patterns of digital story presentation.
Keywords: Problem Solving Based Learning; Digital Story's; Computer Skills; static graphics; animations